2014
DOI: 10.1097/igc.0000000000000111
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Viral Prevalence in Invasive Vulvar Cancer Specimens From Human Immunodeficiency Virus–Positive and -Negative Women in Botswana

Abstract: Objective The primary aim of this study is to describe the prevalence of select oncogenic viruses within vulvar squamous cell carcinoma (VSCC) and their association with Human Immunodeficiency Virus (HIV) status in women in Botswana, where the national HIV prevalence is the third highest in the world. Methods/materials A cross-sectional study of biopsy-confirmed VSCC specimens and corresponding clinical data was conducted in Gaborone, Botswana. Polymerase Chain Reaction (PCR) and Immunohistochemistry (IHC) v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Indeed, the strength of the vulva and penis cancer associations lends support to a causal effect of HIV‐related immunosuppression, for which a IARC working group deemed data were too scarce to be sure of a causal association with HIV in 2012 2. Of note, HIV positivity was 39% in 29 vulva cancers in Rwanda, and 76% in a series of 54 cases from Botswana 27. Findings for anal cancer were consistent with the established causal link with HIV,2 but cases were too few to see a statistically significant association.…”
Section: Discussionmentioning
confidence: 64%
“…Indeed, the strength of the vulva and penis cancer associations lends support to a causal effect of HIV‐related immunosuppression, for which a IARC working group deemed data were too scarce to be sure of a causal association with HIV in 2012 2. Of note, HIV positivity was 39% in 29 vulva cancers in Rwanda, and 76% in a series of 54 cases from Botswana 27. Findings for anal cancer were consistent with the established causal link with HIV,2 but cases were too few to see a statistically significant association.…”
Section: Discussionmentioning
confidence: 64%
“…However, we used a PAF of 100% because it is established that HPV is a necessary cause of cervical cancer ( 16 , 34 ). For vulvar cancer, we found a Botswanan study with a sample size of 35 which reported an HPV prevalence of 100% ( 17 ). However, we used a PAF estimate of 40% obtained from meta-analyses for developing countries, because of the small sample size used in that study ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…12 Individual HPV genotypes are sequenced and grouped according to their predilection for various sites of infection. 14 15 In addition, circulating HPV-16-specific CD4+ and CD8+ T-cells have been shown to be able to migrate from the circulation to the epithelium upon antigenic challenge in healthy subjects. A classification system has been developed to group HPV genotypes based on the important distinction between HPV genotypes that have the potential to cause malignancy and those that do not have the potential to cause malignancy.…”
Section: Classificationmentioning
confidence: 99%
“…13 HPV-related cancers are estimated to account for 5.2% of the worldwide cancer burden, and approximately 3-3.5% of these are caused by HPV-16. 14…”
Section: Classificationmentioning
confidence: 99%